Putting Americans First: A Statistical Case for Encouraging Rather than Impeding and Devaluing US Citizenship. (December 2019) - Kerwin, Donald; Warren, Robert
Executive Summary: This article examines the ability of immigrants to integrate and to become full Americans. Naturalization has long been recognized as a fundamental step in that process and one that contributes to the nation's strength, cohesion, and well-being. To illustrate the continued salience of citizenship, the article compares selected characteristics of native-born citizens, naturalized citizens, legal noncitizens (most of them lawful permanent residents [LPRs]), and undocumented residents. It finds that the integration, success, and contributions of immigrants increase as they advance toward naturalization, and that naturalized citizens match or exceed the native-born by metrics such as a college education, self-employment, average personal income, and homeownership. It finds that: Naturalized citizens enjoy the same or higher levels of education, employment, work in skilled occupations, personal income, and percentage above the poverty level compared to the native-born population. At least 5.2 million current US citizens — 4.5 million children and 730, 000 adults — who are living with at least one undocumented parent 1 obtained US citizenship by birth; eliminating birthright citizenship would create a permanent underclass of US-born denizens in the future. Requiring medical insurance would negatively affect immigrants seeking admission and undocumented residents who ultimately qualify for a visa. About 51 percent of US undocumented residents older than age 18 lack health insurance. In 2017, about 1.2 million undocumented residents lived with 1.1 million eligible-to-naturalize relatives. If all the members of the latter group naturalized, they could petition for or expedite the adjustment or immigration (as LPRs) of their undocumented family members, including 890, 000 "immediate relatives." Their naturalization could put 11 percent of the US undocumented population on a path to permanent residency. The article also explores a contradiction: that the administration's "America first" ideology obscures a set of policies that impede the naturalization process, devalue US citizenship, and prioritize denaturalization. The article documents many of the ways that the Trump administration has sought to revoke legal status, block access to permanent residence and naturalization, and deny the rights, entitlements, and benefits of citizenship to certain groups, particularly US citizen children with undocumented parents. It also offers estimates and profiles of the persons affected by these measures, and it rebuts myths that have buttressed the administration's policies. For example, the Trump administration and restrictionist legislators have criticized the US immigration system's emphasis on family reunification for its supposed failure to produce skilled workers. Yet the article finds that: The current immigration system, which prioritizes the admission of the nuclear family members of US citizens and LPRs, yields a legal foreign-born population that has occupational skills equal to those of the native-born population. The legal foreign-born population living in 24 US states and Washington, DC, and those from 94 source countries 2 have higher percentages of skilled workers than the overall population of native-born workers.